Guide to physics problems - Cahn, Sidney B.; Mahan, Gerald D.; Nadgorny, Boris E. (New York, Plenum Press, 1994)
An excellent study resource, this second of two volumes features 182 problems taken from Ph.D. exams at notable American universities and Moscow "Phys-Tech". Like its acclaimed companion, Part 2 presents detailed solutions with step-by-step calculations, textbook references for further study, clear illustrations, and an easy-to-use layout.
Appendices 335-346p.; Bibliography 347-349p.
Keywords: Physics-Problems; Physics